Strengthening Capacity of Local Government for Prevention of Corruption Apparatus Through Sufi Governance Approach - Trisnawati, Trisnawati (Badan Penerbitan Jurnal (BPJ) FIA-UB, 2016)
Indonesian bureaucracy issues were patched through bureaucratic reform program which is a requirement of post-crisis economic reforms in 1997. Bappenas insists that other areas of reform will not run properly without first reforming the government bureaucracy. Bureaucratic reforms launched by the government it is still not able to fix the bureaucratic culture, is particularly pressing bureaucracy tends to corrupt behavior. Source bureaucratic disease can basically identified two loci, namely internal and external (Irawati, 2012). Internally, the incidence of corrupt behavior within the bureaucracy is also due to weak internal control systems. Therefore the necessary tools to change the bureaucratic apparatus spirituality as the prevention and eradication of corruption. This is where the future will be a mystic governance tools to Overcome corruption. Sufi governance solution offered is to rely on a true monotheism. Because of monotheism is true then the bureaucrats in charge of serving the community will carry out their duties in a comprehensive manner; as which ones have been listed in the code of ethics of the bureaucracy, and he will always see the task as a trust rather than a means to accumulate wealth and depriving the people it serves.